Students’ Perception on The English Teachers’ Pedagogic Competence at British English School - Syamsuddin Syamsuddin; Risma Genisa; Fentry Hernaningsih Ruing (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study was aiming to analyze the perception of the students on their English teachers’ pedagogical competence who handled the Conversation for Adults Classes at Basic Conversation Level in British English School Makassar. Most of the students at this level still have low English competence and consider that English is difficult. The pedagogic competence of the teachers is related to the success of the learning activities. Therefore, it is required to analyse the teachers’ pedagogic competence based on the students’ perception since this affects to their attitude and actions in learning activities. The population of this study was 100 Adults students of British English School who participated in Basic Conversation Class from January to February 2024. The sample of this study was 50 students taken by using purposive sampling technique. The instrument used in this study is a non-test instrument consisting of 25 items of statements to measure students’ perception on English Teachers’ pedagogical competence. From the data processing, the result of the research was (1) Based on statements, obtained 52% in very good category, 20% in good category, 24% in enough category, 4% in less category, 0% in very less category; (2) Based on indicators, obtained 73.04% good category for learning preparation, 68.35% in good category for presentation of learning materials, 74.8% in good category for learning approach/strategy, 91.87% in very good category for students involvement learning, 70.4% good category for design and do the evaluation and 57.4% in good category for utilize assessment result for quality improvement of learning; (3) overall, the student’s perception on English teachers’ pedagogical competence is 72.64% in good category.